14+8g+9+2g-g=49

Simple and best practice solution for 14+8g+9+2g-g=49 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 14+8g+9+2g-g=49 equation:


Simplifying
14 + 8g + 9 + 2g + -1g = 49

Reorder the terms:
14 + 9 + 8g + 2g + -1g = 49

Combine like terms: 14 + 9 = 23
23 + 8g + 2g + -1g = 49

Combine like terms: 8g + 2g = 10g
23 + 10g + -1g = 49

Combine like terms: 10g + -1g = 9g
23 + 9g = 49

Solving
23 + 9g = 49

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add '-23' to each side of the equation.
23 + -23 + 9g = 49 + -23

Combine like terms: 23 + -23 = 0
0 + 9g = 49 + -23
9g = 49 + -23

Combine like terms: 49 + -23 = 26
9g = 26

Divide each side by '9'.
g = 2.888888889

Simplifying
g = 2.888888889

See similar equations:

| -9n=-36 | | Y+15=11whatisy | | 5-6x+3=38 | | y-(-3)=-2x-5 | | 2(m-8)+9=3(4-m)-4 | | f(2c)=3(2c^2)+6(2c) | | -7.8=-1.4x+2 | | 6+4=120 | | -4p-5.2=11.1 | | 4x-13x-19=-73 | | f(x)=-7x^2+5x+7 | | 4x-45=3 | | f-12.3=-73.8 | | 4x-9+2x-1=14 | | -6m-6=24 | | 3x^2-36x-10=o | | 5x-6z=-17 | | 13x+8y=123 | | y-2=.75x-6 | | 6x+5+7x-3=28 | | 15+4n=9n | | -8x-22=23-5x | | 19x+1=x+37 | | -3(2x-6)=12 | | A^2-12a-13=0 | | 9(3)-(-6)+7= | | 2x-12=2+x | | 64c^2=25 | | 2(7+x)=-36 | | b/5+1/3=17 | | 11x=16500 | | (7+x)=-36 |

Equations solver categories